Performance of Urochloa and Megathyrsus Forage Grasses in Smallholder Farms in Western Kenya - Mwendia, Solomon Waweru; Odhiambo, Ruth; Juma, Alfred; Mwangi, David; Notenbaert, An (Frontiers in Sustainable Food Systems, 2021)
Livestock productivity has remained low in sub-Saharan African countries compared to other places on the globe. The feeding component is the major limitation, in both quantity and quality. Among other inputs, feeding takes 55–70% of the costs involved. Livestock play a major role especially in smallholder mixed farms through provision of household nutrition and income through milk and meat. Equally, fertilization of cropland benefits from livestock manure, and livestock often act as insurance and savings by providing liquidity for unforeseen and urgent financial needs. Increasing livestock productivity would enhance the fore-mentioned benefits contributing to well-being and livelihoods. Toward this endeavor and with smallholder dairy farmers' participation, we undertook an evaluation of 10 selected forages from Urochloa Syn. Brachiaria and Megathyrsus syn. Panicum genus and compared them with Napier grass, i.e., Cenchrus purpureus Syn. Pennisetum purpureum commonly grown by farmers. For detailed and robust evaluation, we established the species in eight trial sites spread in four administrative counties in Western Kenya (Bungoma, Busia, Kakamega, and Siaya). In each site, the forages were established in plots in a randomized complete block design, replicated three times. Each site was linked to a group of farmers interested in dairy. For 2 years, dry matter production, plant height, and leaf-to-stem ratio was determined across all sites. Further, we guided farmers to generate participatory forage evaluation criteria, which they later administered across their respective forage demonstration sites individually on plot-by-plot basis to generate preference rating compared to what they normally grow—Napier grass. The results showed significant differences across the forage types within and between the sites. Cumulative dry matter yields ranged 13.7–49.9 t/ha over 10 harvestings across forage types and the counties, while values for crude protein were 1.85–6.23 t/ha and 110,222–375,988 MJ/ha for metabolizable energy. Farmer preferences emerged that highlighted forages with likely better chances of adoption with weighed scores ranging 5.5–7.6 against a scale of 1–9, across the counties. The observations provide additional and well-performing forage options for the farmers and possibly in similar production systems and ecologies. Awareness creation targeting livestock and dairy producers would be key, reaching, and informing them on alternative forage options, with potential to increase livestock productivity.